Dinâmica de glyphosate em plantas de eucalipto - Castro, Edicarlos Batista de [UNESP] (2015)
Eucalyptus is the most used forest species in reforestation in the country due to the rapid growth of plants, climatic conditions and developed technologies. However, interference by the weeds cause major damage, the quantitative and qualitative decrease in production of eucalyptus. Among the weed management possibilities, the chemical method is the most used, however, there are few herbicides registered for eucalyptus cultivation, in which glyphosate is most commonly used to control a large number of species. There are few studies regarding the direct and indirect effects of the glyphosate on this forest species. In this paper, Eucalyptus urograndis clones were subjected to direct contact with glyphosate and indirectly through application on Brachiaria decumbens plants, aiming to characterize the movement of the herbicide, root exudation and its effects on the plant. Visual evaluations were carried out through eucalyptus phytointoxication at 7, 14 and 21 DAA and of the dry mass of the plants at 21 DAA. Also, measurements were made on different parts of plants (top and bottom) of the following compounds by high-performance liquid chromatography and mass spectrometry (LC-MS / MS): glyphosate, aminomethylphosphonic acid (AMPA), shikimic acid, shikimate-3-phosphate, phenylalanine, tyrosine and tryptophan. Glyphosate was detected in eucalyptus plants for treatments with the direct and indirect application of herbicide and there was a translocation to sites that were not attain in the application, even when applied to the B. decumbens, however the AMPA was not. The presence of glyphosate on plants, influenced the change in the shikimic acid levels, phenylalanine, tyrosine, tryptophan, and shikimate- 3-phosphate, apart from causing intoxication in eucalyptus plants and reduction of dry mass. Glyphosate was detected in eucalyptus plants after application on the plants of B decumbens with low intoxicication ...